Religious character values in the Animated Film Nussa and Rara by the little giantz and 4stripe productions - Aulia Agustina; Achmad Ruslan Afendi (Institute of Computer Science (IOCS), 2023)
This study aims to explore the formation of religious character in children through animated films, focusing on the Nussa and Rara Animated Film developed by Yuda Wirafianto. The background reflects the urgency of religious character formation in children, which can be influenced by various factors including the family environment and the media they consume, such as animated films. The research method used is library research, using the animated film Nussa and Rara as the primary data source. The main objective of the research is to identify religious character values in the movie, referring to the concept explained by Glok and Stark in Lies Arifah. The results showed that there are five aspects of religious character values in 10 episodes of the animated film Nussa and Rara. These aspects include Religious Beliefs, Performing Religious Obligations, Spiritual Appreciation, Religious Knowledge, and the Influence of Religious Behavior. By using content analysis techniques, this research provides an in-depth description of the Islamic messages contained in the animated film Nussa and Rara, which can play a role in shaping children's religious character.